Microsurgery Training Resource Variation among US Integrated Plastic Surgery Residency Programs - Mueller, Melissa A.; Pourtaheri, Navid; Evans, Gregory R. D. (Journal of Reconstructive Microsurgery, 2019)
Background Given emerging focus on competency-based surgical training and work-hour limitations, surgical skills laboratories play an increasingly important role in resident education. This study was designed to investigate educational opportunities in microsurgery across integrated residency programs.Methods Senior residents (PGY 4–6) at integrated plastic surgery programs were surveyed during the 2016 to 2017 academic year to determine each program's access to: training microscopes and anastomosis models, video-based skills assessment, pre-requisite skills exams, flap courses, or a formal microsurgical training curriculum. Programs were stratified based on large size (>18 residents) and presence of microsurgery fellows. Chi-squared analysis was performed with p < 0.05 to assess statistical significance.Results Survey responses were collected from 32 of 60 eligible programs (53% response rate). Sixty-nine percent provide access to one to two training microscopes, 25% provide three or more, and 6% provide none. Sixty-nine percent of programs train anastomosis with nonliving prosthetics, 66% with living biologics, and 50% with nonliving biologics. Large program size or having microsurgical fellows was not associated with increased access to training microscopes or specific anastomosis models. Programs without microsurgery fellows reported more often that a formal microsurgery curriculum would be helpful (90 vs. 58% of programs with fellows, p = 0.0003). Respondents who indicated that creating a formal curriculum would not be helpful elaborated that their program already has a formal curriculum or a high volume of microsurgery cases.Conclusion This study demonstrates the current variation in microsurgery training at integrated plastic surgery residency programs. A formal microsurgical training curriculum is commonly viewed as being helpful, particularly at programs without microsurgery fellows.
Keywords: microsurgical training resources; plastic surgery residency; microsurgery fellowship; surgical skills laboratories